ALAT BANTU PENGINGAT DIGITAL BAGI TUNA NETRA MENGGUNAKAN ARDUINO MEGA - Muhammad Nasrul Haq; Faisal Akib; Nur Afif (AGENTS: Journal of Artificial Intelligence and Data Science, 2021)
The senses are a collection of receptors that frame the extraordinary organs or instruments found in the human body, one of the most important of which is the sense of sight. If a person has a disturbing influence on the sense of sight, their activities will be severely limited because the data obtained will be less than those who have ordinary vision. One way to get information is by using the sense of hearing. However, the media that support these obstacles are still severely constrained. Even so, they still have the right to obtain their rights as humans, including the right to information and activities. The purpose of this study is to design a device with a clock function in the form of Braile numbers with an alarm feature so that it can solve the problem of the lack of time information media for blind people. In conducting this research, the type of research used is qualitative research with experimental methods, because it develops a tool and conducts research in the form of experiments on the object of the author's research. The results of this study are in the form of a tool that can remind people with visual impairments or what is called a Digital Reminder / Smart Box Braile tool